P118 The role of the retinoic acid pathway in human lung regeneration. (2nd December 2011) - Ng-Blichfeldt, J P; Griffiths, M; Griesenbach, U; Allen, B; Hind, M
Abstract : Recent studies into retinoic acid (RA)-induced alveolar regeneration in rodent models of emphysema and bronchopulmonary dyplasia strongly suggest a latent regenerative potential of the adult mammalian lung. RA signalling is known to have an important role during alveolar formation in the developing lung in rodents and man. However, critical differences between animal and human physiology and development qualify the relevance of animal models of regeneration. Here we explore the role of RA signalling in human lung regeneration. Using RT-PCR with primers specific to RA signalling genes, we confirm expression of the RA synthesising enzymes Raldh1, 2 and 3, RA degrading enzymes Cyp26 A1, B1 and C1, retinoic acid receptors RAR-α, β, γ and retinoid binding proteins CRBPI and II, and CRABP I and II in normal, human peripheral lung tissue. To determine which cell types of peripheral lung are involved in RA signalling we have isolated primary alveolar type 2 epithelial cells and primary vascular endothelial cells and confirm expression of RA signalling genes. We have developed an high performance liquid chromatography (HPLC) method to identify and quantify endogenous human lung retinoids and demonstrate the ability to separate known standard retinoids by characteristic elution times. Finally, using precision cut lung slices we are developing an experimental system to determine the effects of retinoids in an architecturally complex human tissue model. Future work will include characterisation and optimisation of a primary human type 2 alveolar epithelial cell wound healing model and the effects of various selective retinoic acid receptor agonists and antagonists.